Analysis of Economic Factors Affecting the Financing of Bank Syariah Indonesia (BSI) in 2014–2024 - Shoolihah, Muhayyijah Fil Qurbah; Setyono, Joko; Rahmawati, Mega (Journal of Business Management and Islamic Banking, 2025)
Research Aims: This study aims to analyze the effect of macroeconomic variables on the total financing distributed by Bank Syariah Indonesia (BSI) during the period 2014–2024. The independent variables examined include the Statutory Reserve Requirement (GWM), Financing to Deposit Ratio (FDR), inflation, interest rates, and money supply. Design/methodology/approach: The research employs a quantitative approach with a descriptive-causal method and uses multiple linear regression analysis as the data analysis technique. The data are secondary in nature, obtained from BSI annual reports, official publications of Bank Indonesia, and the Central Bureau of Statistics. Research Findings: The findings indicate that inflation and GWM have a negative effect on total financing, while interest rates, money supply, and FDR have a positive effect. These results largely align with economic theory, although an anomaly is observed in the positive relationship between interest rates and financing, which theoretically should be negative. Theoretical Contribution/Originality: This study contributes to the understanding of the relationship between macroeconomic conditions and financing activities in Islamic banking, particularly highlighting the unique dynamics of Bank Syariah Indonesia within the Indonesian macroeconomic context. Research limitation and implication: The study is limited to the period 2014–2024 and focuses only on selected macroeconomic indicators. Future research could expand the scope by incorporating additional variables or employing different econometric models. The findings provide practical implications for policymakers and banking practitioners in formulating strategies to strengthen the resilience of Islamic banking amid macroeconomic fluctuations.